2022
DOI: 10.1155/2022/4880151
|View full text |Cite|
|
Sign up to set email alerts
|

A Multicenter Cohort Study on Children Suffering from Acute Lymphoblastic Leukemia: Effects of Obesity on Mortality

Abstract: Background. Overweight and obesity have been reported in specific patients and disease survivors compared to other types of childhood cancer. This study is aimed at determining the effect of children’s obesity on the mortality of acute lymphoblastic leukemia. Method. Children admitted to Inner Mongolia International Mongolian Hospital from 1 January 2017 to 31 December 2020 participated in this study. 1070 children were analyzed. A multi-middle-class poll was conducted. All children under the age of 15 were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…Existen otros estudios realizados en población pediátrica de diferentes países con resultados similares, que evalúan el IMC al momento del diagnóstico; Wang et al 26 , en población china, reportó que los pacientes con sobrepeso y obesidad tienen un alto riesgo de mortalidad precoz, así como de una menor supervivencia. Egnell et al 28 , en población nórdica, halló que los pacientes con obesidad tuvieron peor supervivencia global y supervivencia libre de enfermedad.…”
Section: Discussionunclassified